Factors associated with medication adherence in school-aged children with asthma. Issue 1 (31st March 2016) - Chan, Amy H.Y.; Stewart, Alistair W.; Foster, Juliet M.; Mitchell, Edwin A.; Camargo, Carlos A.; Harrison, Jeff
Adherence to preventive asthma treatment is poor, particularly in children, yet the factors associated with adherence in this age group are not well understood. Adherence was monitored electronically over 6 months in school-aged children who attended a regional emergency department in New Zealand for an asthma exacerbation and were prescribed twice-daily inhaled corticosteroids. Participants completed questionnaires including assessment of family demographics, asthma responsibility and learning style. Multivariable analysis of factors associated with adherence was conducted. 101 children (mean (range) age 8.9 (6–15) years, 51% male) participated. Median (interquartile range) preventer adherence was 30% (17–48%) of prescribed. Four explanatory factors were identified: female sex (+12% adherence), Asian ethnicity (+19% adherence), living in a smaller household (−3.0% adherence per person in the household), and younger age at diagnosis (+2.7% for every younger year of diagnosis) (all p<0.02). In school-aged children attending the emergency department for asthma, males and non-Asian ethnic groups were at high risk for poor inhaled corticosteroid adherence and may benefit most from intervention. Four factors explained a small proportion of adherence behaviour indicating the difficulty in identifying adherence barriers. Further research is recommended in other similar populations. Girls of Asian ethnicity, small household size and younger diagnosis age have better adherence to asthma http://ow.ly/Z1y6Q